Recursos ociosos e pontos de estrangulamentos no setor de infraestrutura de transporte no estado do Paraná - Rippel, Nilmar (2021)
The interpretations related to the economic development, often do not acknowledge the existence of Idle Resources and Choke Points in underdeveloped economies likewise, since those can easily be denied or threated as irrelevant to the development process. The transports infrastructure sector (specially the railroader) in Paraná state in the last decades did not respond in kind to the agro-industrial necessities of the country, becoming a choke to the development. Accordingly, Ignácio Rangel inspired by Keynes shows a huge worry about the carelessness those themes are faced, considering the key to the workers escape from the spoliation which they are exposed to in economic crisis periods. Therefore, this research’s goal is to analyze the idle resources and choke points in the transport’s infrastructures in Paraná state from 2000 to 2018. Thus, the research is divides in tree chapters. On the first one, it was made a rescue of Ignacio Rangel’s main ideas, as well as a deliberation about the technology and the State on development promotion. On the second chapter, Paraná state was more focused, noticing that in the last 15 years the state went through specially an intense agricultural growth, which resulted in a bigger pressure to the modes of transport, bringing about a choke specially on the railroad mode because of low investments on its technological refit. On the third chapter, analyzing the idle resources on this sector, the railroad modal dynamism was remarkable (that relativized its choke) hence it was aided mainly by the logistical structure as the information technologies, the port investments, incorporation of formal workers and the storage network distributed by the state. In this way, the capacity installed on the storage network contributed to the cargo flows softening the negative impacts to the modals. Nevertheless, it becomes imperative that the Brazilian State retake the planning protagonism, as happened to the Goals Plan, the II Nation Development Plan (II PND) and the Growth Acceleration Program (PAC) to face the idle resources, being them financial or production factors – capital and work – to the choked sector which in this specific case, the railroad modal is the most emblematic.